A novel multimodality anthropomorphic phantom enhances compliance with quality assurance guidelines for magnetic resonance imaging in radiotherapy - Meshal Alzahrani; David A Broadbent; Irvin Teh; Bashar Al-Qaisieh; Emily Johnstone; Richard Speight (Physics and Imaging in Radiation Oncology)
Background and purpose: The use of magnetic resonance imaging (MRI) for radiotherapy (RT) simulation has grown, prompting quality assurance (QA) guidelines by the Institute of Physics and Engineering in Medicine (IPEM) and the American Association of Physicists in Medicine (AAPM). This study compares a novel multimodality anthropomorphic phantom to an American College of Radiology (ACR) phantom for a subset of these MRI-specific QA tests in RT. Materials and methods: A novel 3D-printed multimodality head-and-neck anthropomorphic phantom was compared to an ACR large MRI phantom. IPEM and AAPM-recommended QA tests were conducted, including informatics/connectivity/data transfer, MRI-CT registration, end-to-end QA, and signal-to-noise ratio (SNR)/percentage integral uniformity (PIU) assessments using RT accessories. Results: Both phantoms were suitable for informatics/connectivity/data transfer. In MRI-CT registration, no errors were found; the ACR phantom offered more quantitative landmarks, while the anthropomorphic phantom provided limited structures. Both phantoms achieved target registration errors (TREs) below 0.97 mm and dice similarity coefficient (DSC) values above 0.9, meeting guidelines. For end-to-end QA, the anthropomorphic phantom facilitated dose measurements of 1.994 Gy versus a calculated 2.01 Gy (−0.8 %). SNR and PIU assessments showed higher values in radiology setups compared to RT setups for both phantoms. Conclusions: Multimodality anthropomorphic phantoms compatible with dosimetric equipment allow realistic end-to-end QA, unlike the ACR phantom. While the ACR phantom is suitable for informatics and MRI-CT registration, anthropomorphic phantoms better represent clinical scenarios. For comprehensive QA, both ACR and anthropomorphic phantoms are required. Additionally, large field-of-view (FOV) phantoms are crucial for evaluating large FOV MRI distortions.